Diversity, Distribution and Co-occurrence Patterns of Bacterial Communities in a Karst Cave System - Zhu, Hai-Zhen; Zhang, Zhi-Feng; Zhou, Nan; Jiang, Cheng-Ying; Wang, Bao-Jun; Cai, Lei; Liu, Shuang-Jiang (Frontiers in Microbiology, 2019)
Caves are typified by their permanent darkness and a shortage of nutrients. Consequently, bacteria play an important role in sustaining such subsurface ecosystems by dominating primary production and fueling biogeochemical cycles. China has one of the world’s largest areas of karst topography in the Yunnan-Guizhou Plateau, yet the bacteriomes in these karst caves remain unexplored. In this study, bacteriomes of eight karst caves in southwest China were examined, and co-occurrence networks of cave bacterial communities were constructed. Results revealed abundant and diversified bacterial communities in karst caves, with Proteobacteria, Actinobacteria, and Firmicutes being the most abundant phyla. Statistical analysis revealed no significant difference in bacteriomes among the eight caves. However, a PCoA plot did show that the bacterial communities of 128 cave samples clustered into groups corresponding to sampling types (air, water, rock, and sediment). These results suggest that the distribution of bacterial communities is driven more by sample types than the separate caves from which samples were collected. Further community-level composition analysis indicated that Proteobacteria were most dominant in water and air samples, while Actinobacteria dominated the sediment and rock samples. Co-occurrence analysis revealed highly modularized assembly patterns of the cave bacterial community, with Nitrosococcaceae wb1-P19, an uncultured group in Rokubacteriales, and an uncultured group in Gaiellales, being the top-three keystone members. These results not only expand our understanding of cave bacteriomes but also inspires functional exploration of bacterial strains in karst caves.